Soccer shootout - Maddox, Jake (Maddox, Jake. Impact books (Stone Arch Books). Jake Maddox sports story., 2008)
When a new boy joins the Titans soccer team, Berk, who has always played goalkeeper, is challenged for that position and he must decide whether to hold a grudge or act for the good of the team.